2019
DOI: 10.4028/www.scientific.net/kem.819.139
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide-Loaded Nanoemulsion and its Activity against Non-Melanoma Skin Cancer Cells

Abstract: Andrographolide (AG) is a diterpenoid lactone found in Andrographis paniculata leaves and stems. It has excellent activity against various cancer cells, for example, skin cancer cells. However, application of AG for skin cancer treatment in clinical trials is limited due to its poor water solubility. To overcome this problem, oil in water AG-loaded nanoemulsion (AG-NE) would be prepared. The objectives of this study were to investigate physicochemical properties of AG-NE and to determine its activity against n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The process of AHPC-NE was optimized using CCD-RSM and AHPC-NE with excellent physicochemical properties were successfully prepared and characterized. Compared with the AG-loaded NE prepared by Sooksai et al, 39) AHPC-NE exhibited smaller droplet size and higher LC. Notably, the droplet size is critical to the efficacy of the NE.…”
Section: Discussionmentioning
confidence: 66%
“…The process of AHPC-NE was optimized using CCD-RSM and AHPC-NE with excellent physicochemical properties were successfully prepared and characterized. Compared with the AG-loaded NE prepared by Sooksai et al, 39) AHPC-NE exhibited smaller droplet size and higher LC. Notably, the droplet size is critical to the efficacy of the NE.…”
Section: Discussionmentioning
confidence: 66%
“…At specific time intervals At specific time intervals (0, 1,2,3, 4, 5, 10, 15, 20, 24hrs), the samples (1 ml) were collected, and replaced simultaneously with fresh medium to maintain sink conditions. The samples were collected, appropriately diluted, and examined by a UV–visible spectrophotometer at 225 nm ( Sooksai et al, 2019 ). The optimized formulation ANG12 was further studied for release kinetics, particle size analysis, ex-vivo permeation, biocompatibility, cytotoxicity, cell cycle analysis, skin irritability, and in-vivo cellular uptake.…”
Section: Methodsmentioning
confidence: 99%
“…The formulation of AG-NEs used in this study was based on the formulation of AG-NEs, which was previously reported with some modifications [ 4 ]. All AG-NEs contained the same compositions and were prepared by microfluidization technique.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the cytotoxic selectivity, a selectivity index (SI) of the test samples was determined by the following Equation (4): SI = IC50 of normal cells IC50 of cancer cells × 100 (4) where IC50 was a half-maximal inhibitory concentration of the test samples that induce fifty percentage of CV of the tested cells.…”
Section: (%) =mentioning
confidence: 99%
See 1 more Smart Citation